Do Academic Environment and Access to Capital Among University Students Contribute to Entrepreneurial Interest Through Creativity? - Hasdiansa, Ilma Wulansari; Hasbiah, Sitti; Adio, Matthew Olufemi (Universitas Negeri Makassar, 2025)
University students, as prospective graduates, play a critical role in generating new employment opportunities through entrepreneurship. This study investigates whether the academic environment and access to capital contribute to entrepreneurial interest among university students, with creativity acting as a mediating variable. A quantitative research design was employed, involving a sample of 100 students selected using proportional random sampling. Data were collected via an online questionnaire and analyzed using SPSS version 27. The findings reveal that the academic environment has a positive and significant influence on both creativity and entrepreneurial interest. Access to capital positively affects creativity but has a negative and significant direct effect on entrepreneurial interest. Creativity, on the other hand, exerts a positive and significant effect on entrepreneurial interest. Moreover, the academic environment significantly contributes to entrepreneurial interest through creativity. Similarly, access to capital indirectly and positively influences entrepreneurial intention when mediated by creativity. These results suggest that fostering a supportive academic environment and enhancing student creativity can significantly boost entrepreneurial aspirations, even when direct financial access is limited or perceived negatively. The study highlights the strategic role of creativity in translating academic and financial inputs into entrepreneurial motivation within higher education contexts.